Neuroprotective Effect from Stem Bark Extracts of Knema Laurina Against H2O2-and Aβ1-42-induced Cell Death in Human SH-SY5Y Cells - Norsharina, Ismail; Akhtar, Muhammad Nadeem; Maznah, Ismail; Seema, Zareen; Syed Adnan, Ali Shah; Nordin, Hj Lajis; Saiful Nizam, Tajuddin (Taylor & Francis, 2015)
The stem bark extracts of Knema laurina inhibited the hydrogen peroxide (H2O2)- and aggregated amyloid b-peptide 1 –42 length (Ab1 – 42)-induced cell death in differentiated SH-SY5Y cells. Exposure of 250mM H2O2 or 20 mM Ab1 – 42 to the cells for 24 h reduced 50% of cell viability. Pretreatment of cells with ethyl acetate extract (EAE) or n-butanol extract (BE) at 300 mg/mL and then exposure to H2O2 protected the cells against the neurotoxic effects of H2O2. Besides, methanolic extract (ME) at 1 and 10 mg/mL exerted neuroprotective effect on Ab1 – 42-induced toxicity to the cells. These results showed that EAE, BE and ME exhibited neuroprotective activities against H2O2- and Ab1 – 42-induced cell death. Flavonoids (3–6) and b-sitosterol glucoside (8) were isolated from the EAE. Compound 1 was isolated from hexane extract, and compounds 2 and 7 were isolated from dichloromethane extract. All these observations provide the possible evidence for contribution in the neuroprotective effects.